Setting Conservation Priorities for Marine Sharks in China and the Association of Southeast Asian Nations (ASEAN) Seas: What Are the Benefits of a 30% Conservation Target? - Du, Jianguo; Ding, Like; Su, Shangke; Hu, Wenjia; Wang, Yuyu; Loh, Kar-Hoe; Yang, Shengyun; Chen, Mingru; Roeroe, Kakaskasen Andreas; Songploy, Se; Liu, Zhenghua; Chen, Bin (Frontiers in Marine Science, 2022)
Sharks play an important role in marine ecosystems as top predators and have been increasingly accepted in recent years as a group for priority conservation worldwide. However, as one of the regions with the highest marine shark species richness, there is still a limited understanding of shark diversity patterns and conservation needs in China and the ASEAN seas. In this study we applied an ensemble species distribution model of five algorithms to investigate the diversity distribution patterns of 149 shark species in China and the ASEAN seas for the first time. A systematic conservation planning approach involving diversity, scarcity, and biogeographical distinctiveness was used to identify and compare conservation priority settings. Results showed that bathymetry and dissolved oxygen are the most important variables contributing to shark distribution. The distribution pattern of shark species richness peaks on the continental shelves and at 22–26 °N, and a hotspot of shark diversity was identified around the Taiwan Strait. The spatial distribution of shark species in the nine orders and the 72 threatened shark species varies considerably. The existing marine protected area network only protects 2.1% of the ocean, 32.9% of the shark species, and 43.1% of the threatened species, highlighting a substantial conservation gap. Among the conservation priorities identified, the high conservation target scenario (30%) protected only 10%–15% more species than the low conservation target scenario (10%). However, under the high conservation target scenario, the conservation range of species could be tripled. Results showed that low conservation targets were only suitable for addressing the number of protected species, and that high targets would bring about improved outcomes for the number of protected species and the protected range of threatened species. Furthermore, planned priorities with large clump pattern had slightly higher conservation achievements than that with small clumps. The results of this study will contribute to the development of a priority area network for sharks and provide a scientific basis for shark conservation and management in the China and ASEAN Seas.